Value-Added Compound Recovery from Invasive Forest for Biofunctional Applications: Eucalyptus Species as a Case Study - Patricia Gullón; Beatriz Gullón; Gonzalo Astray; Paulo E. S. Munekata; Mirian Pateiro; José Manuel Lorenzo (Molecules, 2020)
From ancient times, the medicinal properties of the different Eucalyptus species are well known. In fact, plants from this family have been used in folk medicine as antiseptics, and to treat different ailments of the upper respiratory tract such as sinus congestion, common cold, or influenza. Moreover, other biological activities were described for Eucalyptus species such as antioxidant and antimicrobial properties. In the last few decades, numerous investigations revealed that the compounds responsible for these properties are secondary metabolites that belonging to the group of phenolic compounds and are present in different parts of the plants such as leaves, bark, wood, fruits, and stumps. The increasing demand for natural compounds that can substitute synthetic antioxidants and the increase in resistance to traditional antibiotics have boosted the intense search for renewable natural sources containing substances with such bioactivities, as well as greener extraction technologies and avant-garde analytical methods for the identification of the target molecules. The literature data used in this paper were collected via Scopus (2001–2020) using the following search terms: Eucalyptus, extraction methods, phenolic compounds, and biological activities. This review collects the main studies related to the recovery of value-added compounds from different Eucalyptus species, as well as their biofunctional applications.